Exosomes From Human Cardiac Progenitor Cells for Therapeutic Applications: Development of a GMP-Grade Manufacturing Method - Andriolo, Gabriella; Provasi, Elena; Lo Cicero, Viviana; Brambilla, Andrea; Soncin, Sabrina; Torre, Tiziano; Milano, Giuseppina; Biemmi, Vanessa; Vassalli, Giuseppe; Turchetto, Lucia; Barile, Lucio; Radrizzani, Marina (Frontiers in Physiology, 2018)
Exosomes, nanosized membrane vesicles secreted by cardiac progenitor cells (Exo-CPC), inhibit cardiomyocyte apoptosis under stress conditions, promote angiogenesis in vitro and prevent the early decline in cardiac function after myocardial infarction in vivo in pre-clinical rat models. The recognition of exosome-mediated effects has moved attempts at developing cell-free approaches for cardiac repair. Such approaches offer major advantages including the fact that exosomes can be stored as ready-to-use agents and delivered to patients with acute coronary syndromes. The aim of the present work was the development of a Good Manufacturing Practice (GMP)-grade method for the large-scale preparation of Exo-CPC as a medicinal product, for a future clinical translation. A GMP-compliant manufacturing method was set-up, based on large scale cell culture in xeno-free conditions, collection of up to 8 L of exosome-containing conditioned medium and isolation of Exo-CPC through tangential flow filtration. Quality control tests were developed and carried out to evaluate safety, identity and potency of both cardiac progenitor cells as cell source and Exo-CPC as final product (GMP-Exo-CPC). Cardiac progenitor cells, cultured in xeno-free conditions, showed a lower doubling-time than observed in research-grade condition, while producing exosomes with similar features. Cells showed the typical phenotype of mesenchymal progenitor cells (CD73/CD90/CD105 positive, CD14/CD20/CD34/CD45/HLA-DR negative), and expressed mesodermal (TBX5/TBX18) and cardiac-specific (GATA4/MESP1) transcription factors. Purified GMP-Exo-CPC showed the typical Nanoparticle Tracking Analysis profile and expressed main exosome markers (CD9/CD63/CD81/TSG101). The GMP manufacturing method guaranteed high exosome yield (>1013 particles) and consistent removal (≥97%) of contaminating proteins. The resulting GMP-Exo-CPC were tested for safety, purity, identity and potency in vitro, showing functional anti-apoptotic and pro-angiogenic activity. The therapeutic efficacy was validated in vivo in rats, where GMP-Exo-CPC ameliorated heart function after myocardial infarction. Our standardized production method and testing strategy for large scale manufacturing of GMP-Exo-CPC open new perspectives for reliable human therapeutic applications for acute myocardial infarction syndrome and can be easily applied to other cell sources for different therapeutic areas.